REFLECTION OF NATIONAL HERITAGE IN THE CINEMA ART OF KARAKALPAKSTAN - Karamanova G.; Dauletnazarova G. (American Journals Publishing, 2022)
The aim of the article is to bring to life our historical and national heritage on the screens through cinematography, and to reveal its educational character.
Keywords: Cinema,